2012
DOI: 10.2220/biomedres.33.309
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-5^|^gamma;2 chain expression is associated with tumor cell invasiveness and prognosis of lung squamous cell carcinoma

Abstract: Our previous study showed that tumor budding is a significant indicator of a poor prognosis in lung squamous cell carcinoma patients. Tumor budding-positive (Bud(+)) cases of lung squamous cell carcinoma (SqCC) showed locally aggressive growth, and the positivity was a useful indicator of the lymph node status and prognosis. The present study focused on the clinicopathologic significance of laminin-5γ2 chain expression for local aggressiveness in lung SqCC. Laminin-5γ2 chain immunohistochemical stains in tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…High LAMC2 was associated with a higher risk of recurrence (P = 0.027) and death (P = 0.012) in ADC but not in SCC (Figure 6f), although others, by stratifying LAMC2 expression based on the stromal types or LAMC2 distribution in tumors, showed that high LAMC2 expression in lung SCC with fibrous stroma composition or in invasive front of SCC was correlated with tumor aggressiveness. 39,40 In line with the latter, overexpression of LAMC2 in H1703, a lung SCC cell line, augmented migration and invasion as compared with mock controls (Supplemental Figure 6a). Whether LAMC2 may have a similar role in lung SCC as in lung ADC remains to be investigated.…”
Section: Resultsmentioning
confidence: 53%
“…High LAMC2 was associated with a higher risk of recurrence (P = 0.027) and death (P = 0.012) in ADC but not in SCC (Figure 6f), although others, by stratifying LAMC2 expression based on the stromal types or LAMC2 distribution in tumors, showed that high LAMC2 expression in lung SCC with fibrous stroma composition or in invasive front of SCC was correlated with tumor aggressiveness. 39,40 In line with the latter, overexpression of LAMC2 in H1703, a lung SCC cell line, augmented migration and invasion as compared with mock controls (Supplemental Figure 6a). Whether LAMC2 may have a similar role in lung SCC as in lung ADC remains to be investigated.…”
Section: Resultsmentioning
confidence: 53%
“…This association is highly expected, concerning that tumor budding is a morphologic marker of tumor invasion and laminin‐5 γ2 is capable to generate a migratory tumor cell phenotype, giving tumor cells the necessary mobility to invade . Several studies have identified the occurrence of tumor budding as an important marker for poor prognosis in epithelial malignancies , including OSCC . Even though higher laminin‐5 γ2 expression has been associated with high‐intensity tumor budding in cancer , to the best of our knowledge, this is the first report showing this association in OSCC.…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have identified the occurrence of tumor budding as an important marker for poor prognosis in epithelial malignancies , including OSCC . Even though higher laminin‐5 γ2 expression has been associated with high‐intensity tumor budding in cancer , to the best of our knowledge, this is the first report showing this association in OSCC. Regardless of the association between higher laminin‐5 γ2 expression and high‐intensity tumor budding, it is important to remark that higher expression of laminin‐5 γ2 was also reported in incipient OSCC, suggesting that it should be important in the early steps of tumor invasion .…”
Section: Discussionmentioning
confidence: 78%
“…Lung cancer is evaluated according to morphological features, including histological type, histological differentiation, pleural invasion, blood vessel invasion and lymphatic invasion (810). Evaluations of cancer in other organs include histological factors, such as the INF pattern and stromal type (4–7,29,30). Therefore, the present study considered it important to evaluate these factors in lung cancer, in combination with the conventional factors.…”
Section: Discussionmentioning
confidence: 99%